The hunchback of Notre Dame - Hahn, Don.; Murphy, Tab.; Trousdale, Gary.; Wise, Kirk.; Alexander, Jason, 1959-; Hulce, Tom, 1953-; Jay, Tony.; Kandel, Paul.; Kimbrough, Charles; Kline, Kevin; Moore, Demi.; Stiers, David Ogden; et al. (Burbank, Calif. : Buena Vista Home Entertainment [distributor, 2002)
Quasimodo ventures from his tower to the joyous festival of fools, but the crowd turns cruel and rejects him because of the way he looks. The gypsy Esmeralda rescues him and he finds himself battling to save the people and the city he loves--while reminding us to see people as they are rather than how they appear.
Originally produced as a motion picture in 1996; re-released as DVD on Mar. 19, 2002.
Based on the novel by Victor Hugo.
Special features: "Making of" featurette; Audio commentary by the producer and directors; Singalong song "Topsy turvy"; multi-language reel "A guy like you"; "Topsy turvy underground" game.
Music, Alan Menken ; lyrics, Stephen Schwartz.
Voices: Jason Alexander, Tom Hulce, Tony Jay, Paul Kandel, Charles Kimbrough, Kevin Kline, Demi Moore, David Odgen Stiers, Mary Wickes.
MPAA rating: G.
Keywords: Quasimodo (Fictitious character) -- Juvenile drama; Esmeralda (Fictitious character) -- Juvenile drama; Toleration -- Juvenile drama; Films for the hearing impaired; France -- History -- Louis XI, 1461-1483 -- Juvenile drama; Paris (France) -- History -- To 1515 -- Juvenile drama; Animated films; Animation